An infant with severe Pertussis: Case Report and literature review - Ignatius Adi Poerwanto (RSUP Dr. Kariadi, 2012)
Background : Pertussis is an acute bacterial infection of the respiratory tract caused by Bordetella pertussis. Without immunization and adequate therapy, the disease will evolve to severe complication. The purpose of the case report was to describe the diagnosis and treatment of severe pertussis from a Papuan infant in remote mountainous area of Papua. Case report : A 5 months old male Papuan infant, lived in the mountainous area of Papua was admitted to the hospital after 1 week of cough. No history of DPT immunization. Physical examination revealed continuous coughing, sunken fontanel, sunken eyes, nasal flaring, chest retraction, and bilateral crackles. Laboratory examination showed white blood count was 87,600/ÂµL, CRP 48 mg/dL, ASTO negative. He deteriorated and referred to ICU for Mechanical Ventilation. His bronchoalveolar lavage taken at day 10 confirmed Pseudomonas from the culture and Bordetella pertussis by the PCR. Discussion : Children lived in the Honai without enough ventilation at the area of low coverage of immunization are susceptible to pneumonia. This infant was treated with Erythromicin and Ceftriaxon on admission with the idea that they will cover broad spectrum of antibacterial, atypical pneumonia or Pertussis infection. The Sputum culture from bronchoalveolar lavage showed Pseudomonas resistant to Amoxillin and Erythromicin, but sensitive to Amikacin. This finding explains why there was no clinical improvement after 2 weeks of Erythromicin. After changing to Amikacin, the clinical condition improved in 7 days. Conclusions : On the area with low immunization coverage, the pediatrician should consider Pertussis as one of the possible etiology of pneumonia, and start treating early to get the better result and avoid severe complication. It recommeded that all countries should consider expanding vaccination strategies to include adding Pertussis booster doses to pre-school children (4-6 years old), to adolescent and to those specific adults that have the highest risk of transmitting Bordetella pertussis infection to vulnerable infants.